Epigenetic regulation of chronological and replicative longevity in Saccharomyces cerevisiae - Ayling, J (2012)
Ageing and senescence remain among the most intriguing questions in biology. Saccharomyces cerevisiae has become well established as a fertile model system for the investigation of ageing. Remarkable conservation has been found to exist between interventions extending lifespan in higher animals and yeast – genetic, chemical, and nutritional – suggesting a network of common regulatory pathways controlling large-scale shifts in gene expression involved in senescence. While it has been proposed that epigenetic regulation controls these shifts, evidence remains incomplete. To address this question, novel longevity mutants were isolated in S. cerevisiae using a purpose-designed high-precision screen based on ageing culture outgrowth. A novel long-lived mutant in uncharacterised gene YDR026C was discovered and found to participate in a pathway distinct from TOR signalling, but share epistasis with the histone deacetylase SIR2Δ, a well established regulator of replicative longevity and rDNA maintenance. Through equilibrium density centrifugal separation of culture subpopulations, SIR2Δ and Ydr026cΔ cultures were found to demonstrate reduced and improved maintenance of post-diauxic quiescence respectively, previously shown to underlie chronological survival in strains including snf1Δ. Development of a quantified TUNEL-based assay for genome fragmentation indicated early apoptotic-like behaviour in the SIR2Δ strain. Microdissection experiments and sectored-colony assays of strains containing an rDNA-embedded ADE2 reporter determined that Ydr026cΔ cells also exhibit extended replicative lifespan, and reduced recombination at the rDNA spacer region hotspot, abrogated in SIR2Δ strains. SIR2Δ is well established to repress RNA polymerase II-derived transcripts in the rDNA spacer region, including IGS1-R. Northern analysis determined Ydr026c also silences transcription in the spacer, possibly through preventing termination of the main rRNA transcript, interfering with IGS1-R expression. By transformation with a vector overexpressing IGS1-R, partial reconstitution of the SIR2Δ phenotype was observed, including rDNA hyperrecombination, shortened replicative longevity, and higher-order chromatin structure restoration. These data suggests a model whereby non-coding rDNA spacer transcripts epigenetically determine rDNA maintenance through recombination, leading to physiological phenotypes of replicative and chronological ageing.